Stenotrophomonas maltophilia: a rare cause of early onset neonatal sepsis - Soren, Chapay; Jagtap, Snigdha; Malathi, V.; V. V., Lakshmi Aparnadevi (International Journal of Contemporary Pediatrics, 2018)
Stenotrophomonas maltophilia is a rare cause of early onset neonatal sepsis. The extensive resistance of this organism to several antibiotics leaves fewer options for antimicrobial therapy. A few cases were reported in neonates. We present a case of early onset sepsis in a neonate caused by Stenotrophomonas maltophilia. The newborn was born preterm and presented with respiratory distress within two hours of birth. Stenotrophomonas maltophilia is a rare cause early onset neonatal sepsis with significant morbidity and mortality.